Modified Heuristic Clustering Algorithm to Avoid Cardiac Arrest - Habib Alrammahi, Ali Abdulkarem; Obaid Sari, Farah Abbas; N. Alabid, Noralhuda (International Journal of Intelligent Systems and Applications in Engineering, 2022)
Studies have proven that the blockage that may occur in the blood vessels is a direct cause of cardiac arrest and myocardial arrest, so it is necessary to use the results of the application of radiological examination methods of the heart and large blood vessels - X-ray images, ultrasound, MRI. Therefore, the paper proposed a segmentation method based on a new approach to calculating a continuous and accurate membership function using the (Heaviside and Polynomials) function, in order to extract distinct regions in the images, making the analysis process effective and obtaining an accurate diagnosis, as the results proved that the proposed method highlights the important parts of the cardiovascular images more clearly compared to by traditional methods.